As ações em educação ambiental realizadas por Organizações Não-Governamentais no estado de São Paulo: alcances e limitações - Fossaluza, André Santachiara [UNESP] (2015)
The acting of Non-Governmental Organizations (NGOs) especially on environmental and educational fields have grown and become more emblematic during the last decades. Despite the several efforts to analyze the quality of the actions on environmental education developed by them, there is not a relevant amount of researches tha broadly and deeply analyze these issues. Thus, this work aimed to identify and list the Environmental Non-Governmental Organizations (ENGOs) in São Paulo state, identify which of them develop actions on environmental education and analyze those actions based n the Historical-Critical Pedagogy and critical conceptions of environmental education. As research methods, we collected and analyzed documents and conducted semi-estructured interviews based on Content Analysis. We found 276 ENGOs in São Paulo state, among which 175 perform environmental education actions; 44 of these acting ENGOs were interviewed to collect quantitative and qualitative data. The results show the environmental education activities performed by ENGOs in São Paulo state tend to be conservative, isolated and supported by the 1º and 2º sectors of society. The organization of the ENGOs tends to be democratic. Our results agree with the debate which has been brought by other studies and provide empirical data to suggest that the educational work developed by the ENGOs is wide. However, it tends to be qualitatively limited and bring small contribution to create and ecologically balanced and socially fair society when we consider the critical theoretical framework we take for education and envirnmental education